Web-Based Spine Segmentation Using Deep Learning in Computed Tomography Images - Young Jae Kim; Bilegt Ganbold; Kwang Gi Kim (Healthcare Informatics Research, 2020)
ObjectivesBack pain, especially lower back pain, is experienced in 60% to 80% of adults at some points during their lives. Various studies have found that lower back pain is a very common problem among adolescents, and the highest incidence rates are for adults in their 30s. There has been a remarkable increase in using computer-aided diagnosis to assist doctors in the interpretation of medical images. Spine segmentation in computed tomography (CT) scans using algorithmic methods allows improved diagnosis of back pain.MethodsIn this study, we developed a web-based automatic spine segmentation method using deep learning and obtained the dice coefficient by comparison with the predicted image. Our method is based on convolutional neural networks for segmentation. More specifically, we train a hierarchical data format file using U-Net architecture and then insert the test data label to perform segmentation. Thus, we obtained more specific and detailed results. A total of 344 CT images were used in the experiment. Of these, 330 were used for learning, and the remaining 14 for testing.ResultsOur method achieved an average dice coefficient of 90.4%, a precision of 96.81%, and an F1-score of 91.64%.ConclusionsThe proposed web-based deep learning approach can be very practical and accurate for spine segmentation as a diagnostic method.